CELEBRITY ENDORSEMENT: TINJAUAN PUSTAKA SISTEMATIS DAN ANALISIS BIBLIOMETRIK - Rohmadani Safitri; Hanafi Adi Putranto (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
Purpose - A growing number of studies have examined celebrity endorsement over the past several decades; however, comprehensive, in-depth, and systematically structured research on this topic remains limited. Therefore, this study aims to conduct a systematic literature review combined with bibliometric analysis to examine celebrity endorsement based on existing empirical evidence. Design/Methodology/Approach - This study adopts a Systematic Literature Review (SLR) approach by employing the keyword “celebrity endorsement” in article titles, abstracts, and keywords within the Scopus database. The search process identified 1,745 publications published between 1984 and 2025. Data collection was carried out on December 15, 2025, and the retrieved publications were subsequently analyzed using bibliometric techniques supported by VOSviewer software. Findings - Based on the literature review, a total of 833 articles were identified from various academic publication sources. Research activity on this topic has shown significant intensity since 1984, marked by an increasing number of scholarly works produced by researchers. Most of these articles are written in English and published in reputable academic journals. In terms of country contributions, the United States ranks first as the leading contributor of publications. The disciplines most frequently covering these studies include business, management and accounting, social sciences, as well as economics, econometrics, and finance. Research Limitations/Implications - This study relies exclusively on articles indexed in the Scopus database, which may limit the generalizability of the findings. Future studies are encouraged to incorporate additional academic databases, such as the Web of Science, to broaden the scope and enhance the robustness of research outcomes. From a practical perspective, the findings provide valuable guidance for marketers and companies in designing effective promotional strategies through celebrity endorsement, by considering the alignment between the celebrity’s image, brand values, and consumer preferences to achieve optimal marketing impact. Originality/Value - Although research on celebrity endorsement continues to expand globally, comprehensive and integrative studies remain scarce. Accordingly, this study contributes by systematically mapping the intellectual development and future research directions of celebrity endorsement